Existing Conditions of Local Wisdom-Based Fisheries Management in Teluk Paman Timur Village, Kampar Kiri District, Kampar Regency, Riau - Artika, Media; Prianto, Eko; Yuliati, Yuliati (Faculty of Fisheries and Marine, Universitas Riau, 2025)
Fisheries resource management based on local wisdom is passed down through generations, addressing significant challenges like over-exploitation. Teluk Paman Timur Village exemplifies this with its ‘Lubuk Larangan’ model, where specific river areas are designated for fishing prohibition, enforced by the community. This research examines the environmental conditions of water's physical-chemical parameters, the economic and social benefits of ‘Lubuk Larangan,’ and the current fisheries management status in the village. Using qualitative descriptive methods, data was gathered through observations, interviews, and water quality measurements. Results indicate that the ‘lubuk larangan’ system in Teluk Paman Timur is actively maintained. Management falls under the auspices of Ninik Mamak, POKMASWAS, and BPD, benefiting from community support. Economically, ‘Lubuk Larangan’ meets local consumption needs while providing additional income opportunities. Socially, it facilitates gatherings, cooperation, and activities during harvest seasons. Water conditions within ‘Lubuk Larangan’ are favorable, as evidenced by quality parameters like dissolved oxygen, temperature, pH, clarity, current speed, depth, and TDS, which comply with class 2 water quality standards vital for sustaining fishery resources and aquatic life. This governance model, therefore, enhances both ecological health and community resilience, ensuring sustainable fisheries management